Dynamical Regulation Analysis Identifies Molecular Mechanisms of Fuzheng-Huayu Formula against Hepatitis B-Caused Liver Cirrhosis. (28th June 2015) - Chen, Qi-Long; Lu, Yi-Yu; Peng, Jing-Hua; Dong, Shu; Wei, Bin; Song, Ya-Nan; Zhou, Qian-Mei; Zhang, Hui; Liu, Ping; Su, Shi-Bing
Abstract : Fuzheng-Huayu (FZHY) tablet was formulated based on Chinese medicine theory in treating liver fibrosis. A clinical trial has indicated that FZHY can against hepatitis B-caused liver cirrhosis (HBC), but the underlying mechanism of FZHY efficacy is unclear. Here, we report that miRNA expression levels are remarkably changed when FZHY formula was used in HBC patient's treatment as a paradigm of trials. Then, we functionally characterize the significant impact of potential kernel miRNAs by miRNA-target network analysis. Enrichment analysis show that the FZHY formula dramatically effecting the molecular regulated module in HBC. Thus, we infer that FZHY plays a critical function in HBC treatment process and directly regulated many important pathways, including but not limited to cell cycle, p53 signaling pathway, and TGF- β signaling pathway, suggesting a new strategy for investigating the molecular mechanism of FZHY treatment.